Effect of High-Pressure Treatment on Structure and Properties of Invar Fe–35% Ni Alloy - Nadutov, V.M.; Vashchuk, D.L.; Volosevich, P.Yu.; Beloshenko, V.A.; Spuskanyuk, V.Z.; Davidenko, O.A. (Наносистеми, наноматеріали, нанотехнології, 2013)
The effect of uniform high-pressure (HP) treatment on change of the internal structure hierarchy of polycrystalline Invar f.c.c. Fe–35.0% Ni alloy in quenched state and after hydroextrusion (HE) is studied. As shown, the treatment of the quenched alloy by pressure of 2 GPa is accompanied by the relief formation on the cross-section surface that is caused by reorientation of available grains and by a change of grain-boundaries’ state. The increase of density of twins of deformation and the saturation of structural elements by vacancies and dislocations promoting the grain-boundary slipping is revealed. The HP processing of the previously HE treated samples of the Invar alloy (ε =0.96 and 1.12) is not accompanied by notable distinctions in the structures’ hierarchy with the exception of both the decrease of texture and the increase of twins’ density that is caused by partial stress relaxation. Досліджено вплив оброблення всебічним тиском (ВТ) на зміну структурної ієрархії полікристалічного інварного стопу ГЦК-Fe–35,0% Ni в загартованому стані, а також після оброблення гідроекструзією (ГЕ). Показано, що оброблення тиском у 2 ГПа стопу в загартованому стані супроводжується формуванням на поверхнях шліфа рельєфу, що обумовлено переорієнтацією в просторі зерен і зміною стану їх меж. Виявлено збільшення густини двійників деформації і насичення структурних елементів вакансіями та дислокаціями, які сприяють зерномежовому проковзуванню. Оброблення ВТ попередньо деформованих гідроекструзією зразків інварного стопу (ε = 0,96 і 1,12) не супроводжується помітними відмінностями в ієрархії структури, за винятком зменшення текстури і збільшення густини двійників, що є результатом часткової релаксації мікронапружень. Исследовано влияние обработки всесторонним давлением (ВД) на изменение структурной иерархии поликристаллического инварного сплава ГЦК- Fe–35,0% Ni в закалённом состоянии, а также после обработки гидроэкструзией (ГЭ). Показано, что обработка давлением в 2 ГПа сплава в закалённом состоянии сопровождается формированием на поверхностях шлифов рельефа, обусловленного переориентацией в пространстве зёрен и изменением состояния их границ. Обнаружено увеличение плотности двойников деформации и насыщение структурных элементов вакансиями и дислокациями, способствующими зернограничному проскальзыванию. Обработка ВД предварительно обработанных гидроэкструзией образцов инварного сплава (ε = 0,96 и 1,12) не сопровождается заметными различиями в иерархии структуры, за исключением уменьшения текстуры и увеличения плотности двойников, являющихся результатом частичной релаксации микронапряжений.